Catalytic non-thermal plasma treatment of endocrine disrupting compounds, pharmaceuticals, and personal care products in aqueous solution: A review. (March 2022) - Nam, Seong-Nam; Choong, Choe Earn; Hoque, Shamia; Farouk, Tanvir I.; Cho, Jinwoo; Jang, Min; Snyder, Shane A.; Meadows, Michael E.; Yoon, Yeomin
Abstract: Contaminants of emerging concerns such as endocrine-disrupting compounds (EDCs) and pharmaceuticals/personal-care products (PPCPs) constitute a problem since they are not completely eliminated by traditional water and wastewater treatment methods. Non-thermal plasma (NTP) is considered as one of the most favorable treatment methods for the removal of organic contaminants in water and wastewater. The degradation of selected EDCs and PPCPs of various classes was reviewed, based on the recent literature, to (i) address the effect of the main NTP treatment parameters (water quality and NTP conditions: pH, initial concentration, temperature, background common ion, NOM, scavenger, gas type/flow rate, discharge/reactor type, input power, and energy efficiency/yield) on the degradation of contaminants and their intermediates, (ii) assess the influences of different catalysts and hybrid systems on degradation, (iii) describe EDC and PPCP degradation along with their properties, and (iv) evaluate mineralization, pathway, and degradation mechanism of selected EDCs and PPCPs for different cases studied. Furthermore, areas of potential research in NTP treatment for the degradation of EDCs and PPCPs in aqueous solutions are recommended. It could be reasonably predicted that this review is valid for developing our understanding of the fundamental scientific principles concerning the catalytic NTP of EDCs and PPCPs, providing helpful and practical references for researchers and designers on the effective removal of EDCs/PPCPs and the optimized operation of catalytic NTP systems. Graphical abstract: Image 1 Highlights: Catalytic non-thermal plasma treatment of contaminants of emerging concern was reviewed. Catalytic non-thermal plasma treatment performance was significantly influenced by water quality and NTP conditions. Areas of future research in catalytic non-thermal plasma treatment were suggested.